Midwifery Care for Postpartum Mothers with Discomfort of Abdominal Pain (Afterpain) in the Maternity Home: Asuhan Kebidanan pada Ibu Postpartum dengan Ketidaknyamanan Nyeri Perut (Afterpain) di Rumah Bersalin - Mustafidah, Nilna Mawaddatul; Djauharoh, Djauharoh; Cholifah, Siti (Indonesian Journal of Innovation Studies, 2020)
Abdominal pain (afterpain) is pain that occurs after childbirth that lasts 2-3 days caused by contraction and relaxation of the uterus sequentially and continuously. Usually most often occurs in multiparous mothers and breastfeeding mothers. If not noticed will have a negative impact on the mother and baby. The purpose of this midwifery care is to find out midwifery care for postpartum mothers with abdominal discomfort (afterpain) at the maternity home and the Tanggulangin Sidoarjo mother clinic. The method implemented is using a descriptive method whose main purpose is to describe a situation objectively by using SOAP approach and documentation. Results and discussion found no gaps between theory and real cases. The conclusion is obtained by carrying out midwifery care independently and in collaboration with early resolution, there are no complications in the postpartum period, healthy mothers and babies and babies receive exclusive breastfeeding.